Open Intraperitoneal Onlay Mesh (IPOM) Technique for Incisional Hernia Repair - Köckerling, Ferdinand; Lammers, Bernhard (Frontiers in Surgery, 2018)
Abstract In an Expert Consensus Guided by Systematic Review the panel agreed that for open elective incisional hernia repair sublay mesh location is preferred, but open intraperitoneal onlay mesh (IPOM) may be useful in certain settings. Accordingly, the available literature on the open IPOM technique was searched and evaluated. Material and Methods A systematic search of the available literature was performed in July 2018 using Medline, PubMed, and the Cochrane Library. Forty-five publications were identified as relevant for the key question. Results Compared to laparoscopic IPOM, the open IPOM technique was associated with significantly higher postoperative complication rates and recurrence rates. For the open IPOM with a bridging situation the postoperative complication rate ranges between 3.3% and 72.0% with a mean value of 20.4% demonstrating high variance, as did the recurrence rate of between 0% and 61.0% with a mean value of 12.6%. Only on evaluation of the upward-deviating maximum values and registry data is a trend towards better outcomes for the sublay technique demonstrated. Through the use of a wide mesh overlap, avoidance of dissection in the abdominal wall and defect closure it appears possible to achieve better outcomes for the open IPOM technique. Conclusion Compared to the laparoscopic technique, open IPOM is associated with significantly poorer outcomes. For the sublay technique the outcomes are quite similar and only tendentially worse. Further studies using an optimized open IPOM technique are urgently needed.